Multi-level issues in organizations and time - Dansereau, Fred, 1946-; Yammarino, Francis J., 1954- (Research in multi level issues ;, 2007)
This volume contains three main themes. The first theme relates to financial developments in the MENA region, emphasizing the role of stock markets and portfolio flows, foreign direct investments and private and public savings in the growth and development experience of the region. We see echoed throughout the first few chapters the notion that financial liberalization has many benefits as well as risks not only for the countries involved, but for international investors as well. For the countries of this region, we see the promise of enhanced growth and development through more developed financial markets that can facilitate the important relationship between investors and savers. For the international investor, we see a region that is posed to offer returns that are strongly correlated to risk. In the developing economies of the MENA region commercial banks have played a prominent role in economic growth since capital markets are still underdeveloped and still lack the appropriate mechanisms to channel effectively and efficiently funds from surplus units to deficit units. The next theme of the volume relates to the role commercial banks have played in channelling funds from savings to investments, and their role in the financing for development experience of some MENA economies. Finally, and on a broader level, the conduct of monetary policy in some MENA countries is highlighted with some emphasis on exchange rate policies and the use of some exchange rate regimes and their impact on the economies of the region.